2022
DOI: 10.1113/jp281556
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of A. V. Hill's Nobel Prize winning work on muscle energetics

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…The definition of a Hill-type model has been continuously refined and extended since Hill’s preliminary Nobel prize-winning works (Hill, 1922; Hill, 1938; Barclay & Curtin, 2022), as detailed in SM1. A Hill-type model refers today, consistently with the terminology proposed in milestone reviews in the field (Zajac, 1989; Winters, Jack M., 1990; Epstein, 1998), to any rheological arrangement of an active force generator (FG), which builds the active muscle force, and in-series and in-parallel MT passive elements, which passively transmit force through the stretch-resisting dynamics of their constitutive material.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of a Hill-type model has been continuously refined and extended since Hill’s preliminary Nobel prize-winning works (Hill, 1922; Hill, 1938; Barclay & Curtin, 2022), as detailed in SM1. A Hill-type model refers today, consistently with the terminology proposed in milestone reviews in the field (Zajac, 1989; Winters, Jack M., 1990; Epstein, 1998), to any rheological arrangement of an active force generator (FG), which builds the active muscle force, and in-series and in-parallel MT passive elements, which passively transmit force through the stretch-resisting dynamics of their constitutive material.…”
Section: Methodsmentioning
confidence: 99%
“…The 1938 paper wasn’t Hill’s last word on the topic. After time spent on war-related activities (for descriptions, see Barclay and Curtin 2022 ; Katz 1978 ; Rall 2017 ), Hill returned to science in the late 1940s. Following further developments of his heat-measuring apparatus (Hill 1949a ), Hill showed that more energy, as both heat and work, was produced in twitches with shortening (Hill 1949b , 1953 ), correcting an earlier anomalous result (Hartree and Hill 1928a ).…”
Section: A V Hill’s Ultimate Response: Empirical Confirmation Of Fenn...mentioning
confidence: 99%
“…Contemporary estimates for mitochondrial efficiency are closer to 80%, whereas that of the cross‐bridge efficiency seems to greatly depend on species and fibre type (Barclay 2017). However, in any case, and when considering the additional energy used for ion transport, the maximum overall efficiency values for human muscle are expected to be well below 30% (Barclay, 2017, 2019; Barclay & Curtin, 2022). Here, it may be emphasized that these are maximum theoretical values, that is, the maximum efficiency possible under optimal experimental conditions, which probably do not occur during whole‐body tasks such as cycling (Barclay et al., 2010).…”
Section: Introductionmentioning
confidence: 99%